Diabetes Mellitus and Associated Factors Among Adult HIV Patients on Highly Active Anti-Retroviral Treatment - Duguma F (Dove Medical Press, 2020)
Fanta Duguma,1 Waqtola Gebisa,1 Aklilu Mamo,1 Desalegn Adugna,2 Shiferaw Woyesa1 1School of Medical Laboratory Sciences, Faculty of Health Sciences, Jimma University, Jimma, Ethiopia; 2Department of Nutrition and Dietetics, Faculty of Public Health, Jimma University, Jimma, EthiopiaCorrespondence: Shiferaw Woyesa Email bekeleshiferaw@yahoo.comBackground: Highly active anti-retroviral therapy (HAART) prolongs the life span of people living with HIV (PLWHIV) and intensely reduces HIV-related morbidity and mortality. Globally, HIV-associated non-communicable diseases are becoming major public concerns, and chronic comorbidities have appeared as a substantial reason for morbidity and mortality in HIV patients with prolonged use of HAART.Purpose: A cross-sectional study design was used to assess the magnitude of diabetes mellitus and risk factors among adult HIV patients exposed to HAART at Jimma Zone Public Hospitals from May to July 30, 2018.Patients and Methods: A convenient sampling technique was used to include a total of 271 adult HIV patients on HAART visiting the selected health facilities at the time of data collection. Socio-demographic and clinical data were collected by interviewer-administered questionnaire and by reviewing patients’ record data. Bivariate and multivariate logistic regressions were used to identify variables that are independent predictors for diabetes mellitus.Results: The prevalence of diabetes and pre-diabetes among PLWHIV exposed to HAART was 11.4% and 16.6%, respectively. The prevalence of diabetic dyslipidemia in PLWHIV exposed on HAART was 8.9% (n=24). Government workers (AOR: 0.17, 95% C.I=0.03– 0.85, P=0.031), long duration in HAART use (AOR: 11.06, 95% C.I:1.03– 18.67, P=0.047), hyper-triglyceridemia (AOR: 2.62,95% C.I:0.82, 8.39, P=0.005), LDL-C < 130 mg/dl (AOR: 4.04, 95% C.I=1.33– 12.30, P=0.014), and obesity (AOR: 9.62, 95% C.I: 1.01– 91.52, P=0.049) were independent risk factors for diabetes mellitus in PLWHIV exposed to HAART.Conclusion: Exposure to HAART increased the prevalence of diabetes mellitus in PLWHIV although it enhances quality of life, improves immune functions and prevents the onset of opportunistic infections. Therefore, regular screening for blood glucose level for PLWHIV on HAART is advisable.Keywords: diabetes mellitus, dyslipidemia, prevalence, HAART, risk factors